Influence of polybag size and watering regimes on growth of hevea brasiliensis Mull. Arg. Seedlings in three soil series - Abu Bakar, Noorsuhaila (2015)
Hevea brasiliensis or rubber planting has shifted to the dry marginal land. This can give rise to a higher plant death or damage during field transplanting, requiring immediate replacement of dead plants especially young Hevea seedlings. By adopting high quality planting material and high yielding clones could reduce ortality, reduce immaturity period of Hevea tree and replace dead seedlings during transplanting. Appropriate polybag size should be determined to be used as planting material for establishment of an advanced planting material (APM) in nursery. Thus, an experiment was conducted to investigate the growth performance and suitability of two clones, RRIM 2025 and RRIM 3001 in different polybags sizes for commercial cultivation. Small polybag sizes inhibit greatly plant height and girth circumferences for both clones. Meanwhile, large polybags encouraged vigorous root growth as more elongate root was developed to enhance water and nutrient uptake. Root development was closely associated with the volume of soil within two polybags size as shown in root:shoot ratio. Root: shoot ratio increased linearly to increase in size of polybags. Plant shoot growth was inhibited more in small polybags than the roots despite the restricted rooting space. Root length and root volume were also significantly influenced by polybag size. This suggests that a reduction in polybag sizes reduced growth performance as reflected by the growth rate of H. brasiliensis at the nursery stage. It was concluded that a large polybag results in vigorous performance for rubber seedlings, and that it would be ideal for use in raising young-budded Hevea tree as advanced planting material before establishment in the field. Comparison between clones, clone RRIM 3001 was recommended for planting purpose due to its vigor during establishment stage and its capability to produce more roots which lead to search water and nutrient effectively on dry marginal land. However, study on watering regimes is needed for new LTC which is lacking in literature review. In experiment 2, the response of latest clone of Hevea brasiliensis towards water stress on different soil series was investigated. The shoot and stem dry weight of Hevea clone decreased significantly with decrease watering frequencies. The highest values for shoot and stem dry weight were found in wellwatered treatment. However, no significant difference was observed between soil series. Root:shoot ratio was significantly greater under treatment withholding water for eight days especially plants when grown on Munchong Series compared to Serdang and Sungai Buloh Series soil due to fine texture which encourages root development within soil. Photosynthesis rate was significantly lower in treatment of watering intervals every eight days. This accompanied with reduction in stomatal conductance and transpiration rate. However, water use efficiency was greater under treatment of watering intervals every eight days. This indicates the ability of plants to conserve water during stress. Total leaf area significantly decreased as watering intervals increased and affected Fv/FM ratio. In conclusion, water stress strongly affected growth and physiological characteristics of RRIM 3001 grown in different soils in Malaysia. Different soil series did not affected by water stress. However, in case of planting clone RRIM 3001 for rubber production, both clay and sandy clay soil like Munchong and Serdang Series soils provide good conditions for crop establishment and not sandy soil like Sungai Buloh Series soil. The objective in experiment 3 is to study the effects of different field capacity and soil series on growth and physiological response of Hevea brasiliensis, RRIM 3001. Plants grown on Munchong Series soil recorded the highest value for plant height, plant girth, leaves dry weight, total leaf area and chlorophyll content followed by Serdang, then Sungai Buloh Series soil series. Overall plant receiving higher level of field capacity recorded significant higher in plant height, plant girth, leaves dry weight, stem dry weight, total leaf area, chlorophyll content, photosynthesis rate and stomatal conductance as compared with plants receiving lower level of field capacity. The root to shoot ratio of clone RRIM 3001 increased when subjected to decrease level of field capacity. Photosynthesis rate and stomatal conductance was reduced when applying excess water. Thus, water requirement for each soil series was differed and full capacity level is not enough to sustain plant growth especially in dry marginal land and facing environmental stress.